Histórias de um trauma: memórias, testemunhos e ficção sobre a guerra de Canudos - Tarcísio Fernandes Cordeiro (2020)
This research consists a study about the narratives related to the Canudos war and the representations of the backland imaginary. The key issue is directed to the different ways of remembering that traumatic experience, when considering, especially, the focus of the testimonial content. In order to do so, a comparative reading between three moments of the war reports takes place, namely: the first one is related to the inaugural writing, impacted by the violence of direct observation, in which the visual appeal of the historical witness, the testis, predominates in productions elaborated by State assistants; the second concern to the work of Euclides da Cunha, Os sertões: campanha de Canudos (1902), in which the meanings of the unspeakable and the imaginary pathos are fixed in the canon; the last one refers to two reports by survivors and the manuscripts by Antônio Conselheiro that characterize another reading of war events, from the perspective of superstes and martis, centered on affective memories that relate to oral culture and religious tradition. Taken together, such accounts tension contemporary memorialistic fiction to rewrite the symbology of that extreme event. In this way, the study verifies the role played by literature in the social perlaboration of traumatic images in societies, such as the Brazilian, which face problems in dealing with the historical past.